A review of institutional response and Covid-19 pandemic risk communication in regional autonomy system in Indonesia - Agus Supriyadi; Tao Wang; Pandu Pribadi; Mochammad Ali Mauludin; Faqih Ma'arif; Zalik Nuryana (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
A global pandemic Covid-19 led countries to take aggressive action regarding social management and crisis governance management system. The case of a pandemic discovered in Wuhan provides a lesson for the government worldwide to adopt. However, the government system in every country has its characteristics. This study aims to release the potential policy recommendation in Indonesia when Indonesia's regional autonomy system faces a challenge in the pandemic situation, such as the increase of competition between regions. Even more, the public service system becomes concerned with the ego regionality. The strengthening country's capacity system is vital in the regional autonomy system as well as the collaboration between central and local government in terms of containment of the spread of the pandemic. Used a political ecology approach and a descriptive- review method, this study was conducted by discussing how the government responds in the regional autonomy system at the beginning of the pandemic situation. The review results show that the local government's response relies on their capacities, such as budget, human resources, and leadership. However, challenges arise when central and local governments' action is not in line in terms of the regional autonomy system. The public and political communication among central and local governments should be rearranged with an integration under proper management, particularly in the first month of the pandemic situation.